1999
DOI: 10.1007/s000180050433
|View full text |Cite
|
Sign up to set email alerts
|

Geminivirus DNA replication

Abstract: Geminiviruses are DNA viruses which infect plants. They have a small genome and encode only a few proteins. Therefore, their DNA replication cycle relies largely on the use of cellular DNA replication proteins. The strategy used by geminiviruses to replicate their single-stranded DNA (ssDNA) genome consists of a first stage of conversion of ssDNA into double-stranded DNA (dsDNA) intermediates and, then, the use of dsDNA as a template to amplify viral dsDNA and to produce mature ssDNA genomes by a rolling-circl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
160
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(180 citation statements)
references
References 142 publications
1
160
0
4
Order By: Relevance
“…These relatively simple pathogens amplify their genomes in the nuclei of host cells by a rolling-circle replication mechanism that uses double-stranded DNA intermediates as replication and transcription templates (Bisaro, 1996;Gutierrez, 1999;Hanley-Bowdoin et al, 1999). Because geminiviruses do not encode a DNA or RNA polymerase, viral replication and transcription depend almost entirely on cellular machinery.…”
Section: Introductionmentioning
confidence: 99%
“…These relatively simple pathogens amplify their genomes in the nuclei of host cells by a rolling-circle replication mechanism that uses double-stranded DNA intermediates as replication and transcription templates (Bisaro, 1996;Gutierrez, 1999;Hanley-Bowdoin et al, 1999). Because geminiviruses do not encode a DNA or RNA polymerase, viral replication and transcription depend almost entirely on cellular machinery.…”
Section: Introductionmentioning
confidence: 99%
“…The dsDNA is used as a substrate in which 13 -16 superhelical turns are introduced by association with histone octamers (Pilartz and Jeske 1992), much in the same way as it occurs with SV40 DNA. In the second stage, new viral ssDNA molecules are produced by a rollingcircle mechanism (Gutierrez 1999;Saunders 2008). The viral initiator protein (Rep) is a multifunctional protein with origin-specific DNA binding, homo-and heteroligomerization, and helicase and endonuclease activities (reviewed in Jeske 2009).…”
Section: Geminivirus Dna Replicationmentioning
confidence: 99%
“…These viruses have circular, single-stranded, monopartite or bipartite DNA genomes replicating in the nucleus through a combination of rolling-circle and recombination-mediated mechanisms (Gutierrez, 1999;Preiss and Jeske, 2003). Based on genome organization and number of components, the type of vector and host plants, seven geminivirus genera (Mastrevirus, Curtovirus, Topocuvirus, Becurtovirus, Eragrovirus, Turncurtovirus and Begomovirus) have been identified that comprise most of the known species (Brown et al, 2012;Fauquet et al, 2008;Varsani et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%